Implementación de un programa de inducción y reinducción en seguridad y salud en el trabajo para la empresa Redcomputo ltda. (2020)
This document analyzes the importance of having an induction and reinduction program with the purpose to illustrate and communicate about the policies, standards and risks faced by employees, contractors and suppliers of the company in occupational safety and health (OSH), allowing to improve working conditions. The study methodology used for this research has a qualitative-descriptive approach that allows analyzing both the results of self-evaluation according to the minimum requirements of decree 1072 of 2015, as well as the conditions of employees and other interested parts. As a sample, the company Redcomputo Ltda and its collaborators where the non-compliance of the program was evidenced in accordance with the evaluation of minimum standards of the aforementioned decree, surveys of prior knowledge on safety and health at work were conducted, taking into account the collection of information, the design and implementation of the induction and reinduction program is carried out, the main objective of which is to promote a sense of belonging, self-care and safety for workers, contractors and suppliers; obtaining as a result best practices and procedures in the development of their work functions